Parvovirus B19 induced fulminant liver failure in pregnancy: A rare incidence (Indian Journal of Case Reports, 2019)
Parvovirus B19 (B19V) is a single-stranded DNA virus of the family Parvoviridae and genus Erythrovirus. Parvovirus B19 infection can present with myriads of clinical diseases and syndromes; liver manifestations and hepatitis are examples of them. The majority of the available literature regarding acute parvovirus B19 induced fulminant hepatic failure has described cases involving children. Acute fulminant liver failure caused by acute parvovirus B19 infection in a pregnant lady is rarely reported in the literature. Here, we report a case of fulminant liver failure in a 28-year-old pregnant lady presenting as a diagnostic dilemma, the etiology of which was eventually detected as acute Parvovirus B19 infection. Since Parvovirus B19 is a potential cause of non-A, non-E fulminant hepatic failure, an early diagnosis is of utmost importance as treatment options are limited.